The peso appreciation and monetary-fiscal coordination - Gerardo P. Sicat (University of the Philippines, School of Economics (UPSE), 2012)
The Philippine peso appreciation has been creating serious problems for the economy because of the high degree of unemployment and poverty incidence in the country. More specifically, it threatens contraction of the export sector through loss of competitiveness. The paper tracks the exchange rate experience of the Philippines with four other East Asian neighbors and finds that the Philippine appreciation is most severe. The paper asserts that exchange rate policy is a matter of policy discretion even under the regime of market-based exchange rates. Options for monetary policy in curtailing domestic liquidity are discussed. Finally, the options for improved coordination of monetary and fiscal policy are suggested.
Keywords: 330; Philippine peso exchange rate; exchange rate appreciation; monetary policy; fiscal policy; Philippine economic development; Wechselkurs; Währung; Aufwertung; Finanzpolitik; Wirkungsanalyse; Philippinen